2021
DOI: 10.3126/ajms.v12i4.35153
|View full text |Cite
|
Sign up to set email alerts
|

A study on etiology, clinical profile and outcome of acute febrile encephalopathy in children: A prospective study at a tertiary care center of Eastern India

Abstract: Background: Acute febrile encephalopathy (AFE) is defined as fever associated with acute alteration of consciousness, with or without seizure, motor and/ or sensory deficit and total duration of illness one week or less. It is associated with significant morbidity and mortality in children. Various etiologies have been implicated in its causation and differ as per geographical. Efforts to promptly identify the underlying etiology and institute appropriate treatment early and adequately should be our goal so as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…7 The average duration of fever reported was slightly more in study done by Biswas et al who found mean duration of 4.62 days. 14 In our study, average duration of altered sensorium was 19.07 hours whereas the illness duration was 16.2±7.9 days. In the present study, refusal to feed was seen in only 6 patients (17.1%).…”
Section: Resultsmentioning
confidence: 43%
See 1 more Smart Citation
“…7 The average duration of fever reported was slightly more in study done by Biswas et al who found mean duration of 4.62 days. 14 In our study, average duration of altered sensorium was 19.07 hours whereas the illness duration was 16.2±7.9 days. In the present study, refusal to feed was seen in only 6 patients (17.1%).…”
Section: Resultsmentioning
confidence: 43%
“…Deepthi reported neck stiffness in 44 (52.4%) cases. 9,14 In the month of November maximum cases 8 (22.9%) were seen. Most of the cases were reported during monsoon period, followed by post-monsoon and pre-monsoon.…”
Section: Resultsmentioning
confidence: 91%
“…CSF has a similar electrolyte composition to plasma, except that the former contains less K+, a lower pH, and a greater Cl-content. 1,5 CSF has a protein content of around 250 mg/L. In general, the CSF is devoid of antibodies and complements.…”
Section: Discussionmentioning
confidence: 99%
“…AFE is one of the commonly encountered problems by the physician in emergency departments. 1 There are distinct regional and seasonal variations in the symptoms and prognosis of AFE. Bacterial meningitis (BM), Japanese encephalitis (JE), cerebral malaria (CM), and typhoid encephalopathy are the common types of AFE and result in fever with an altered mental state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation